FAKTOR – FAKTOR GEOGRAFI YANG MENDUKUNG PENGEMBANGAN OBJEK WISATA DANAU SEBEDANG DI KECAMATAN SEBAWI KABUPATEN SAMBAS - Muhammad Ridha Surista; Nuraini Asriati; Diah Trismi Harjanti (Universitas Tanjungpura, 2022)
This study aims to determine the potential, the factors that influence the development, and the efforts made in the effort to develop the Sebedang Lake tourist attraction. This research is expected to be a reference for the government in determining the direction of development and management of the Sebedang Lake tourism object. The type of this research is descriptive research with quantitative methods which is carried out on the Sebedang Lake tourist attraction, Sebawi District, Sambas Regency. The collection techniques used in this study were observation, interviews, questionnaires, and documentation. The analytical technique used is scoring with an interval scale and descriptive analysis. Tourism potential is assessed based on three classifications, namely supportive, moderate, and not supportive. Based on the research that has been done, it shows that the potential for natural tourist attractions is 77.08% (supporting), artificial tourist attractions 100 (moderate), accessibility 63.33 (not yet supported), accommodation 77.77 (supporting), infrastructure 310 (moderate), and sapta pesona 215 (support). Based on these results, it shows that the Sebedang lake tourism object has problems in developing a tourist attraction because it has not supported several geographical factors. To overcome these problems, the manager makes various efforts to develop Sebedang lake attractions, such as building lodging, and eco-friendly artificial tourist attractions, as well as conducting dialogue and lobbying to ask for funding assistance from related parties such as the tourism office, etc.